Teacher Strategies in Installing Independent Character in High School Elementary School Students in Learning - Elpinora, Elpinora; Riscaputantri, Anggarwati; Ade, Jimoh Azeeh (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to analyze teacher strategies in instilling independent character in students in Elementary Schools. Methodology: A qualitative approach with descriptive design was used in this study, with a population of teachers at elementary schools Terbansari I selected by purposive sampling. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. Main Findings: The results of the study showed that project-based learning strategies, small group discussions, and active parental involvement through digital communication were effective in increasing student independence. The main challenge faced by teachers was the habit of students relying on teacher direction. Teachers overcame this by providing individual guidance and rewards to encourage student motivation. Novelty/Originality of this study: The novelty of this research lies in the integration of project-based learning strategies with reflective activities and direct parental involvement in character learning in Elementary Schools.